Synthesis of Mixed‐Functionalized Tetraacylgermanes. Issue 10 (1st December 2020) - Püschmann, Sabrina D.; Frühwirt, Philipp; Pillinger, Michael; Knöchl, Andreas; Mikusch, Marlene; Radebner, Judith; Torvisco, Ana; Fischer, Roland C.; Moszner, Norbert; Gescheidt, Georg; Haas, Michael
Abstract: Tetraacylgermanes are known as highly efficient photoinitiators. Herein, the synthesis of mixed tetraacylgermanes 4 a –c and 6 a –e with a nonsymmetric substitution pattern is presented. Germenolates are crucial intermediates of these new synthetic protocols. The synthesized compounds show increased solubility compared with symmetrically substituted tetraacylgermanes 1 a –d . Moreover, these mixed derivatives reveal broadened n–π* absorption bands, which enhance their photoactivity. Higher absorption of these new compounds at wavelengths above 450 nm causes efficient photobleaching when using an LED emitting at 470 nm. The quantum yields are in the range of 0.15–0.57, depending on the nature of the aroyl substituents. On the basis of these properties, mixed‐functionalized tetraacylgermanes serve as ideal photoinitiators in various applications, especially in those requiring high penetration depth. The synthesized compounds were characterized by elemental analysis, IR spectroscopy, NMR and CIDNP spectroscopy, UV/Vis spectroscopy, photolysis experiments, and X‐ray crystallography. The CIDNP data suggest that the germyl radicals generated from the new tetraacylgermanes preferentially add to the tail of the monomer butyl acrylate. In the case of 6 a –e only the mesitoyl groups are cleaved off, whereas for 4 a –c both the mesitoyl and the aroyl group are subject to α‐cleavage. Abstract : Just mix it ! Mixed‐functionalized tetraacylgermanes were synthesized by two innovative pathways. These new derivatives outperform the state‐of‐the‐art germanium based photoinitiators in terms of both solubility and absorption properties.